ALIGNING MULTIPLE TRANSLATIONS IN AN AUTHOR PARALLEL CORPUS OF A. S. PUSHKIN POETRY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
The article presents a method for aligning several published English translations of one Pushkin poem against the Russian source within an author parallel corpus. As material, two anchor texts are used, namely the opening stanza of Eugene Onegin in eight verse translations (H. Spalding 1881 through S. Mitchell 2008) and the lyric Ya vas lyubil in twenty English versions. Comparing five alignment algorithms (W. Gale and K. Church 1993, R. Moore 2002, HunAlign 2005, Bleualign 2010, Vecalign 2019), the study records 0.90 F1 for Vecalign on the reference benchmark. Stand-off TEI P5 encoding stores line-level correspondences across all translations at once.